ANALISIS CEK LIST KESELAMATAN DAN KESEHATAN KERJA DI LABORATORIUM BIOLOGI FMIPA UNNES - Ria Ika Maharani; Fitri Arum Sasi (UIN Sunan Kalijaga Yogyakarta, 2018)
Occupational safety and health in the laboratory becomes very important considering the laboratory has a high risk of accident. Assessment of the risk of accidents in the laboratory cover many components, such as chemicals, equipment, supporting factors and users. With a high level of risk, the application of occupational safety and health needs to be monitored and assessed. The purpose of this study was to analyze the safety and health of the laboratory in biology based on the check list of safety and health reference. The method used is descriptive in the form of questionnaires with data analysis using categories based on normative values that is x ≥ 67.5 category is very good, 45 ≤ x <67.5 good category, 22.5 ≤ x <45 category good enough and x ≤ 22 , 5 categories are not good. The conclusion of the research is occupational safety and health in the biology laboratory included in the good category with the average score 57.28. This shows that based on the reference matrix of safety and health check list in the laboratory consisting of laboratory layout, office, personal protective equipment, hygiene, emergency tool, chemicals, glassware and electricity have been done well.